REGIONAL FOOD CULTURE OF INDIA: HISTORICAL PERSPECTIVE (International Journal of Food and Nutritional Sciences, 2022)
Evolution of human culture is a perennial process resulting from their encounter with nature and the aspiration to explore ways to live more effectively. From the prehistoric times, the needs to survive hunger and the challenges of nature have led to innumerable inventions. Human progressed from hunting-gathering nomadic beings to food producing, food processing and food trading beingsin the longrun. The environmental conditions, availability of fauna and flora in the habitation had contributed in the formulation of agricultural practices and food culture of every society and this culture are ever evolving. This paper explores into the diversity of food culture across regions of India in a historical perspective and argues that it is the habitat setting that fundamentally formulate the food culture of a society.